Causality of ICT Expenditure on Financial Performance in Indonesia’s Logistics and Courier Sector, 2020–2024 - Imma Ismaniar; Muhammad Fikry Januar; Dede Ibrahim Maulana; Solihin; Eko Prasetyo; Astri Julianari (Politeknik Mardira Indonesia, 2026)
ICT investment has emerged as a strategic imperative for Indonesia’s logistics sector, propelled by e-commerce acceleration and post-pandemic demands for operational efficiency. This study analyzes the causal relationship and potential